Artikel Review Fitokimia: Efektivitas Infusa sebagai Metode Ekstraksi - cha, charles06; Nisful lailatun nadiroh (PC Ikatan Apoteker Indonesia (IAI) Karanganyar, 2025)
Extraction is a fundamental process in isolating bioactive compounds from natural materials that is crucial for the development of pharmaceutical, food, and cosmetic products. Infusion as one of the conventional extraction methods uses water solvent at approximately 90°C for 15 minutes which is widely used due to its simplicity, does not require complex equipment, is economical, and is capable of extracting polar compounds effectively. This review aims to comprehensively examine the working principles of the infusion method based on the diffusion process of bioactive compounds, factors affecting extraction effectiveness, advantages and disadvantages of the method, applications on various groups of phytochemical compounds, and recent innovations in method modification. The review method was conducted through literature searches from Google Scholar, Garuda, and PubMed using keywords